TINDAKAN MENYAMARKAN IDENTITAS PELAKU KEJAHATAN (Tinjauan Undang-Undang Nomor 40 Tentang Pers dan KUHP) - Orin Gusta Andini (Universitas Teuku Umar, 2016)
The purpose of this research is to know the vague of crime perpetrator identity by journalist from law number 40/1990 on Pers and Penal Code Perspective and to know the rule of police in enforcing the law related to vague of crime perpetrator identity in observuing journalist investigation result. The type of this research field is filed research in which data collection done by interviewing several parties related to research. Besides, writer also make literature research through related data and books. Then, data taken is analysed qualitatively and explained descriptively.Based on analysis, writer conclude that: very side interpretation on rejection right is legal weakness that can be used by journalist to do action which vague identity if crime perpetrator. The action of vague crime perpetrator identity fey on Artivle 165 Indonesia Penal Code which oblige every citizen to report known to police officer. The usage of rejection right by journalist not suit to article 165 Indonesia Penal Code that can be used to vague informan identity who is witness, child crime perpetrator and rape victim as journalist ethic code. Keywords: The Vague of Perpetrator Identity, Journalist, Law Number 40/1999 on Pers, Indonesian Penal Code.